Recent advances in carbon dots for bioimaging applications. Issue 2 (28th October 2019) - Li, Hongxia; Yan, Xu; Kong, Deshuai; Jin, Rui; Sun, Chunyan; Du, Dan; Lin, Yuehe; Lu, Geyu
Abstract : This review summarized recent advances in CDs-based bioimaging including in vitro imaging in delivering CDs into different types of cells and in vivo applications in distribution and uptake of CDs, imaging-guild drug delivery and tumor therapeutics. Abstract : As an important member of fluorescence nanoparticles, carbon dots (CDs) not only possess exceptional chemical properties, including excellent biocompatibility, low toxicity and chemical inertness, but also exhibit promising optical properties, such as broad excitation spectra, tunable emission spectra and high photostability, thus attracting tremendous attention. Over the past decade, applications of CDs in numerous fields have been intensively investigated, ranging from biomedical analysis to optoelectronics and energy. Among these cutting-edge applications, this review article mainly outlines recent advances in the field of CD-based bioimaging and summarizes achievements in two broad categories: in vitro imaging in terms of the approaches to deliver CD-based probes into different types of cells and vital cell organelles, as well as in vivo applications that focus on distribution and uptake of CDs in mice and zebrafish, imaging-guided drug delivery and tumor therapeutics. Furthermore, the potential superiority, challenges and future directions of CDs for imaging are also presented. The purpose of this review is to highlight the importance of CD-based bioimaging and to boost its development in diverse research fields ranging from materials science to biomedicine.